(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الصحية, 2019)
This study was conducted at Tishreen Hospital University in Lattakia in the department of obstetrics and gynecology between 1/1/2016 -1/1/2017 The study sample consisted of 270 caesarean sections, which were administered for a patient with one caesarean section. • The first group is 78 patients wish modern caesarean section. • The second group is 192 patients with classic cesarean section. The study conducted a comparison between the two groups. The results were as follows: 1- The percentage of adhesions in the first group was 41% while in the second group 48.9%2- We did not notice any significant difference in the thickness of LSCS between the two groups using abdominal ultrasound.§ good scar which their thickness ≥ 3 mm The rate of good scars of first group were 84.6%. The rate of good scars of second group were 82.2%.3- There were short mess of the time of caesarean about (7 – 11) minutes by the modern cesarean and short mess of the time of delivery at least 3-4 minutes. أجريت هذه الدراسة في قسم التوليد بمشفى تشرين الجامعي ما بين 1/1/2016 -1/1/2017، حيث كانت عينة الدراسة مؤلفة من 270 قيصرية أجريت لمريضه باستطباب سوابق قيصرية مع مراعاة طريقة إجراء القيصرية الأولى • المجموعة الأولى 78 مريضة أجريت القيصرية الأولى بالطريقة الحديثة • المجموعة الثانية 192 مريضة أجريت القيصرية الأولى بالطريقة التقليدية قامت الدراسة بإجراء مقارنة بين المجموعتين في النقاط التالية: 1- نسبة حدوث الالتصاقات بالإضافة الى شدتها وتوضعها 2- ثخانة القطعة السفلية 3- مدة إجراء القيصرية كاملة ومدة استخراج الجنين 4- لم تدرس شدة النزف في كلا الطريقتين لأنها مقدرة عالميا ب 1000 مل في القيصرية بشكل وسطي بغض النظر عن الطريقة وهي تعود في معظمها لانفكاك المشيمة ولصعوبة تقدير الكمية الناجمة عن الجراحة بشكل معزول فكانت النتائج على الشكل الآتي: 1- بلغت نسبة الالتصاقات بالفئة الأولى 41% وبلغت في الفئة الثانية 48,9% 2- لم نلاحظ اختلافا ذو أهمية فيما يتعلق بالثخانة بالنسبة للقطعة السفلية للرحم بين المجموعتين وذلك باستخدام الايكو البطني • الندب الجيدة بالفئة الأولى 84,6% ( ندبة جيدة ≥ 3 ملم ) • الندب الجيدة بالفئة الثانية 82,2% 3- وجد اختصار هام لزمن القيصرية يبلغ وسطيا 7-11 دقيقة في الطريقة الحديثة إضافة لاختصار زمن ولادة الجنين بما لا يقل عن 3-4 دقائق